Groundwater vulnerability in the Piedmont region under climate change - Nistor, Mărgărit-Mircea (2021)
Groundwater vulnerability has increased in recent decades due to several factors, but mainly due to climate change. In this study, we applied a complex approach to determine groundwater vulnerability at a regional scale in the Piedmont region including high-resolution climate models. Aquifers, terrain model, climate data, land cover, and groundwater monitoring stations data of nitrate (NO3) concentration were the main layers used for the vulnerability and risk mapping. Validation of the groundwater vulnerability map consisted of pixel pair comparison (PPC) using the quality status of a monitored groundwater station, dating from 2005 to 2012. The groundwater vulnerability maps that related to the 1990s and 2020s periods indicated very high and high vulnerability of groundwater in the central and eastern parts of the region, especially in the porous aquifers of Po Plain. The areas with very low and low vulnerability extend into the north and west, mainly in the non-aquiferous media and fissured aquifers. The future scenarios of groundwater vulnerability indicate a consistent increase of the very high vulnerability class, from the 1990s to the 2050s periods, in all scenarios, and mainly in the Po Plain.